Information Science and Police Activity: A Necessary Approach - Flávio Zampronha, Luís (Advanced Notes in Information Science, 2023)
Starting from the premise that the exercise of the power to collect data and information is the main activity carried out by the police, the possibility of using the theoretical currents of Information Science in the structuring of police information systems must be assumed. Therefore, this work aims to analyze the types of information managed by the police and the various data sources used by public security agencies. In turn, the model of police action guided by intelligence emphasizes the importance of information as the primary resource to be used by public security agencies in optimizing their activities. It is assumed that all information of interest to public security agencies must be preserved, stored, and mainly consulted. Thus, the procedures and systems used by the police can use the theoretical bases and currents of Information Science with the creation of systems that, in addition to providing access to data and documents efficiently and quickly, reconcile the processing of personal data and the protection of individual rights and informational freedom of citizens.